2010
DOI: 10.1074/jbc.m109.083485
|View full text |Cite
|
Sign up to set email alerts
|

Schizosaccharomyces pombe Dss1p Is a DNA Damage Checkpoint Protein That Recruits Rad24p, Cdc25p, and Rae1p to DNA Double-strand Breaks

Abstract: Schizosaccharomyces pombe Dss1p and its homologs function in multiple cellular processes including recombinational repair of DNA and nuclear export of messenger RNA. We found that Tap-tagged Rad24p, a member of the 14-3-3 class of proteins, co-purified Dss1p along with mitotic activator Cdc25p, messenger RNA export/cell cycle factor Rae1p, 19 S proteasomal factors, and recombination protein Rhp51p (a Rad51p homolog). Using chromatin immunoprecipitation, we found that Dss1p recruited Rad24p and Rae1p to the dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Genetic studies also suggest a broad functionality: yeast lacking Dss1 display pseudohyphal and temperature-sensitive growth ( Jäntti et al., 1999 , Jossé et al., 2006 , Marston et al., 1999 ), impaired mRNA export ( Faza et al., 2009 ), and sensitivity to DNA damage ( Krogan et al., 2004 , Selvanathan et al., 2010 ). In fission yeast, the growth defect is partially suppressed by expression of other proteasome subunits, suggesting that this phenotype is connected to a destabilization of the 26S proteasome ( Jossé et al., 2006 , Mannen et al., 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic studies also suggest a broad functionality: yeast lacking Dss1 display pseudohyphal and temperature-sensitive growth ( Jäntti et al., 1999 , Jossé et al., 2006 , Marston et al., 1999 ), impaired mRNA export ( Faza et al., 2009 ), and sensitivity to DNA damage ( Krogan et al., 2004 , Selvanathan et al., 2010 ). In fission yeast, the growth defect is partially suppressed by expression of other proteasome subunits, suggesting that this phenotype is connected to a destabilization of the 26S proteasome ( Jossé et al., 2006 , Mannen et al., 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Deletion of Brh2 or Dss1 results in radiation sensitivity and recombination deficiency of U. maydis (1921). Although these two proteins contribute to the gamma radiation resistance of U. maydis , the presence of BRCA2 or Dss1 orthologs in radiation-sensitive vertebrates and eukaryotes (2224) indicates that other factors involved in radioresistance remain uncharacterized.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, as mRNA export is coupled to transcription, mRNA splicing and maturation, blocking mRNA export could activate distinct levels of post-transcriptional control and DNA damage recognition (Culjkovic-Kraljacic and Borden, 2013;Wickramasinghe and Venkitaraman, 2016), leading to elimination of the cyst cells. Finally, work in Schizosaccharomyces pombe revealed that the mRNA export and cell cycle regulator Rae1 has a DNA-damage checkpoint function and gets recruited to double-strand breaks along with Cdc25 and Checkpoint kinase 1 (Chk1) (Selvanathan et al, 2010). Thus in addition to its role in mRNA export, Rae1 may also possess a checkpoint function in testis cyst cells and accumulation of Rae1 in cyst cell nuclei, upon block of mRNA export, may result in activation of DNA damage responses in cyst cells depleted of nup62, emb, nup214 or nup88 function.…”
Section: Discussionmentioning
confidence: 99%